The crystal structure of diaqua-methanol-κ1 O- (3-thiophenecarboxylato-κO)-(2,2′-dipyridyl-κ2 N,N′)manganese(II) 3-thiophenecarboxylate, C21H22N2O7S2Mn - Shi Zheng; Zhang Zhongyu; Han Bing; Li Yunyun (Zeitschrift für Kristallographie - New Crystal Structures)
C21H22N2O7S2Mn, monoclinic, P21/c (no. 14), a = 14.544(6) Å, b = 9.636(4) Å, c = 17.087(7) Å, β = 96.664(6)° $96.664(6){}^{°}$ , V = 2378.5(17) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0349, wRref $wR_{ref}$ (F 2) = 0.1036, T = 273.15 K.